PENINGKATAN SOFT SKILL DAN MANAJEMEN TIM BAGI SISWA SMK DALAM MENGHADAPI ERA SOCIETY 5.0 - widiyati, dian; hasanah, neneng; Purnomo, Endri (Jurnal Abdi Citra, 2025)
The Society 5.0 era requires the younger generation to have competence not only in technical aspects, but also interpersonal skills such as communication, leadership, and teamwork. This community service activity was carried out at SMK Techno Media, South Tangerang, with the aim of improving students' soft skills and team management through interactive training based on simulations and case studies. The implementation method consists of planning, socialization, training implementation, evaluation, and follow-up. The results showed a significant increase in students' communication, leadership, and teamwork skills. This program is expected to be a model for soft skill development that can be replicated in other vocational schools.